The Relationship between Social Support and Quarter Life Crisis in Early Adulthood in Kolongan Village, Tomohon City - Sigar, Valerie; Solang, Deetje J.; Sengkey, Marssel M. (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Quarter life crisis is a crisis period in the age range of 18 to 29 years, where a person experiences excessive anxiety and restlessness because they begin to question the direction and purpose of life, as well as the many choices in making life decisions. The power of social support from closest relations such as friends, family or relatives to young adults who are experiencing a quarter life crisis can reduce excessive anxiety and help alleviate what they are worried about, so that they are more confident, more competent and reduce the risk of stress. The subjects of this research are adults. The initial number was in Kolongan Village, Tomohon City, totaling 78 people. The approach used in this research is using a quantitative approach with correlation techniques, which aims to determine the relationship between social support and quarter life crisis in early adulthood in Tomohon Tengah District. The measuring instruments used in this research are the quarter life crisis scale with 35 items (α = 0.941) and the social support scale with 20 items ( α = 0.925). Analysis of the data used was Pearson product moment correlation, obtained a correlation value (r) - 0.165. It can be concluded that there is a significant negative relationship between social support and the quarter life crisis in early adulthood in Kolongan Village, Tomohon City. This means that the higher the social support, the lower the level of individual quarter life crisis, conversely, the lower the social support, the higher the level of quarter life crisis in Early Adults in Kolongan Village, Tomohon City, so this research hypothesis is accepted